Hemorrhagic Fever Occurs After Intravenous, But Not After Intragastric Inoculation of Rhesus Macaques with Lymphocytic Choriomeningitis Virus (2002)
ABSTRACT: Arenaviruses can cause hemorrhagic fever and death in primates and guinea pigs, but these viruses are not highly pathogenic for most rodent carriers. In the United States, arenaviruses precipitated outbreaks of hepatitis in captive monkeys, and they present an emerging health threat in the tropical areas of Africa and South America. We describe infection of rhesus macaques with the prototype arenavirus, lymphocytic choriome-ningitis virus (LCMV), using the WE strain that has been known to cause both encephalopathy and multifocal hemorrhage. Five macaques were inoculated: two by the intravenous (i.v.) and three by the intragastric (i.g.) route. Whereas the two i.v.-inoculated monkeys developed signs and lesions consistent with fatal hemorrhagic fever, the i.g.-inoculated monkeys had an attenuated infection with no disease. Pathological signs of the primate i.v. infection differ significantly from guinea pig arenavirus infections and make this a superior model for human viral hemorrhagic disease.